Integrated omics profiles for exploring the potential mechanism underlying aroma formation in the terpenoid-rich aromatic plant Opisthopappus taihangensis and the bioactivity of its leaf essential oil - Maolin Liu; Yushu Li; Haixia Chen; Chunjie He; Lei Sun; Xiuhai Zhang; Zongda Xu; Hua Liu (Agriculture Communications)
Summary: Opisthopappus taihangensis (Anthemideae, Asteraceae), which is rich in bioactive components, produces flowers and leaves with robust fragrances. In this study, we conducted comprehensive metabolomic and transcriptomic analyses to identify changes in terpenoid metabolites and associated gene expression across various O. taihangensis tissues (leaves, buds, and inflorescences at the exposure, initial-bloom, and full-bloom stages). We identified 1370 metabolites using headspace solid-phase micro-extraction/gas chromatography-mass spectrometry (HS-SPME/GC–MS), 308 of which were terpenoid metabolites. The expression of terpenoid synthesis-related genes was relatively consistent with the synthesis of terpenoid metabolites at each examined developmental stage. An analysis of gene networks governing terpenoid synthesis revealed that MCT genes (OtMCT1, OtMCT2, and OtMCT3), TPS genes (OtTPS5, OtTPS9, and OtTPS10), and OtISPS1 may be crucial for synthesizing specific metabolites in different tissues. Additionally, the essential oil extracted from leaves by water distillation showed that thujone and camphor were the predominant components. The considerable antioxidant activity of the leaf essential oil was comparable to that of vitamin C (16 ​μg/mL). Notably, its antimicrobial effects against Staphylococcus aureus and Escherichia coli growth were greater than those of ampicillin and vancomycin at the same concentrations. Scanning electron microscopy images indicated that the leaf essential oil significantly disrupted bacterial cell structures. This study thoroughly analyzed the network of genes regulating terpenoid metabolites in different O. taihangensis tissues, and elucidated the antioxidant and antibacterial potential of the leaf essential oil, thus providing valuable insights for breeding, molecular characterization, and the potential application of O. taihangensis in developing useful essential oil-based natural products.